Hubungan Pengetahuan Penyakit Menular Seksual (PMS) dengan Tindakan Kebersihan Alat Reproduksi Eksternal pada Wanita Usia Subur - Nur Hayati; Hamsia L Waru (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine the relationship between knowledge of sexually transmitted diseases and external reproductive hygiene practices in women of childbearing age. The research design is a cross-sectional study. Sampling was carried out using non-probability sampling with purposive sampling technique, and the sample size was determined using the Isaac and Michael tables with an error rate of 5% so that a total sample of 32 women of childbearing age was obtained in Liwuto Village, Kokalukuna District, Baubau City from December 2022 to January 2022. The results showed that age characteristics (p = 0.084) had no significant relationship with respondents' knowledge, while education characteristics (p = 0.001) had a substantial relationship with WUS knowledge. While the level of expertise (p-value = 0.001 <α = 0.05) shows a significant connection to external reproductive hygiene practices in WUS. It is hoped that the puskesmas and the health office will continue to improve the provision of health education through counseling on reproductive health.